Relationship between trade enhancement, firm characteristics and CSR: key mediating role of green investment. Issue 1 (31st December 2022) - Weihong, Jiao; Kuo, Tsung-Hsien; Wei, Siao-Yun; Islam, Misbah ul; Hossain, Md. Shamim; Tongkachok, Korakod; Imran, Asma
Abstract: Organisations are increasingly implementing socially responsible strategies in response to increased rivalry in trade and commercial activities. Organisations are expected to increase their profitability through corporate social responsibility (CSR). Hence, this study investigates the relationship between trade enhancement, firm characteristics, and CSR. Further, this study also explored the critical mediating role of green investment (GI). The data were collected from 456 respondents from manufacturing organisations in China through a questionnaire and analysed by partial least square structural equation modelling (PLS-SEM). PLS-SEM results revealed that trade enhancement has a significant positive effect on CSR and GI. GI also has a significant effect on CSR. In comparison, firm characteristics do not have a substantial impact on CSR and GI. However, GI significantly mediates the relationship between trade enhancement, firm characteristics, and CSR. This study provides insights to managers and stakeholders regarding GI and CSR in the Chinese manufacturing industry. Lastly, this study proposes theoretical and practical implications andoffers valuable information for practitioners and policymakers.